Understanding carbon credits from agriculture - Adeeth Cariappa, Ajjikuttira Girish (AESA, 2023)
In this blog, A. G. Adeeth Cariappa discusses how carbon credits can be used to incentivize farmers to adopt measures that can support climate change mitigation and how agricultural extension can spread the word.